Evaluación de dos métodos de castración con dos productos anabólicos en machos bovinos para carne (BRAHMAN X MESTIZO) - Chávez Rivas, Adrián Fernando (2016)
In this study two methods of castration with two anabolic products were evaluated. T1 immune-castration + Synovex, T2 immune-castration + Revalor G), T3 Surgery + Synovex and T4 Surgery + Revalor G. 40 young bulls were used with ± an average weight of 300kg, Brahmin x hallf-breed: Four treatments were used . The data were evaluated by using a randomized complete block design (RCB) with a factorial arrangement treatment 2x2, and 0, 05 Tukey test for comparison of measures. After this they were processed through the statistical package Infostat (2015). As a result of the variables, it is possible to evince in the initial weight (IW), as in the final weight (FW), no statistical difference; on average daily gain (ADG), the T2 obtained 0,70kg / d unlike T4 with 0,54kg / d; and average monthly weight gain (AMG), the T2 averaged 20,93Kg unlike T4 which reported 16,08Kg and the total weight gain (TWG), the T2 reported 83,7kg in 120 / d, being numerically greater than T4 which reported 64,3kg; in the monthly body weight, there is no significant difference. Animals treated with Bopriva and Synovex (T1) obtained a profit of $ 1, 14. Immune-castrated animals obtained levels below normal ranges of cortisol (<9,0ng / dl). Immune-castration is a procedure that meets the objectives of zootechnical and productive interest for fattening systems because it promotes respect and welfare towards animals under a no bloodless treatment, and generates a satisfactory answer in economic terms.